Decreased apoptosis in advanced-stage/high-grade hepatocellular carcinoma complicating chronic hepatitis C is mediated through the downregulation of p21 ras - Baddour, Nahed; Farrag, Ebtehal; Zeid, Ahmed; Bedewy, Essam; Taher, Yousry (Chinese Journal of Cancer Research, 2013)
Objective and background: Although p21 ras has been reported to be upregulated in hepatocellular carcinoma complicating chronic hepatitis C type I, p21 ras has a different role in advanced stages, as it has been found to be downregulated. The goal of this study was to investigate the status of p21 ras in early-stage/low-grade and late-stage/high-grade hepatocellular carcinoma and its possible link to apoptosis. Material and methods: Thirty-five cases each of chronic HCV hepatitis type 4 (group I) and cirrhosis with hepatocellular carcinoma (HCC) complicating chronic HCV hepatitis (groups II and III) were immunohistochemically evaluated using a p21 ras polyclonal antibody. The apoptotic index was determined in histologic sections using the terminal deoxynucleotidyl transferase-mediated d-UTP biotin nick end labeling (TUNEL) assay. Results: Significant differences (P=0.001) were detected in p21 ras protein expression between the three groups. A near 2-fold increase in p21 ras staining was observed in the cirrhotic cases compared to the hepatitis cases, and p21 ras expression was decreased in the HCC group. p21 ras expression correlated with stage (r=0.64, P=0.001) and grade (r=–0.65, P=0.001) in the HCC group and grade in the HCV group (r=0.44, P=0.008). Both p21 ras expression and TUNEL-LI were significantly lower in large HCCs compared to small HCCs (P=0.01 each). The TUNEL values were negatively correlated with stage in the HCC group (r=–0.85, P=0.001). The TUNEL values were also negatively correlated with grade in both the HCV and HCC groups (r=0.89, P=0.001 and r=–0.53, P=0.001, respectively). The p21 ras scores were significantly correlated with the TUNEL-LI values in the HCC group (r=0.63, P=0.001) and HCV group (r=0.88, P=0.001). Conclusions: p21 ras acts as an initiator in HCC complicating type 4 chronic HCV and is downregulated with HCC progression, which most likely promotes tumor cell survival because it facilitates the downregulation of apoptosis with tumor progression.